Ketahanan Keluarga: Dinamika Psikososial dalam Transformasi Nilai dan Struktur Sosial - Noor Syifa Amaliah Azizah (Journal of Health, Medical, and Psychological Studies, 2025)
Family resilience has become a crucial issue in contemporary society as families face rapid transformations in social values, structures, and interaction patterns. This study examines family resilience as a psychosocial and adaptive process shaped by changes in social values and family structures. The findings indicate that psychosocial dynamics, including emotional bonds, communication quality, and internal support systems, play a significant role in strengthening family resilience. The transformation of social values, particularly related to digitalization, gender roles, and economic structures, has reshaped family authority, role distribution, and value internalization processes. Family resilience emerges not as a static condition, but as an adaptive strategy that enables families to negotiate change while maintaining relational stability and core values. Families that demonstrate flexibility, reflective communication, and balanced role negotiation tend to show stronger resilience in responding to social pressures. The study highlights that family resilience functions as a strategic social resource that supports individual well-being and social sustainability. Understanding family resilience from a psychosocial and structural perspective provides a comprehensive framework for strengthening families amid ongoing social transformation